Modelling And Development Of An Improved Sorting System In The Plywood Grading Line - Rasul, Mohamad Sattar (2003)
The main focus of this study is on the sorting method of graded plywood in the grading line. The plywood grading line is the final process in the production line. Due to the inefficiency of the sorting method, this line has low productivity, high labor usage and defectives due to improper sorting of the plywood by the operator. The collected statistics were analyzed and the output analysis deals with drawing the comparison between the existing grading line and the built model. This study has eight aspects measured in order to achieve the objectives. They are; time study, production rate, labor cost, labor productivity, capacity utilization, defective rate, investment cost and downtime. Overall comparison for sorting graded plywood between existing system and proposed systems (pneumatic and hydraulic systems), shows that, the sorting time was reduced to 20.3% using pneumatic sorting system whereas 10.9 % using hydraulic sorting system. Hence increasing the production rate by 38.9% and 32.5% accordingly.